Finding Reliable Information Online: Adventures of an Information Sleuth - Leslie F. Stebbins (Rowman & Littlefield Publishers, 2015)
We live in an information-saturated environment and spend far too much time searching, surfing, skimming, contributing, and organizing the information in our lives. We spend too little time immersing ourselves in reliable high quality information. We are often so buried in information and strapped for time that we grab information like it was fast food, without bothering to evaluate its quality.